“Who blends in and why (not)?” A qualitative study on psychotherapists' patient inclusion in blended care - Sophie Jordan; Pauline Becker; Solveig Behr; Friederike Fenski; Christine Knaevelsrud; Johanna Boettcher; Carmen Schaeuffele (Internet Interventions)
Introduction: Psychotherapists may act as bottlenecks in the integration of digital interventions into psychotherapy, known as blended care (BC). In the literature, various factors are discussed as potential inclusion, exclusion, or limiting criteria in BC. Method: Our aim for this interview study was to gain a deeper understanding of the factors psychotherapists consider when inviting patients to participate in BC. For this purpose, we interviewed seven psychotherapists with a psychodynamic and seven psychotherapists with a cognitive behavioral background who participated in a naturalistic trial on BC in routine outpatient psychotherapy. Results: Psychotherapists considered few fixed inclusion or exclusion criteria when considering which patients to introduce BC to. The basic technical requirements had to be met and the patients had to be “fit for outpatient therapy”. Psychotherapists found patients' response to BC, like their motivation, to be a decisive factor when considering BC. Discussion: Psychotherapists emphasized patient motivation for BC as a potential bottleneck in its implementation. Therefore, a successful implementation strategy should focus on strengthening both psychotherapists' and patients' motivation to engage with BC. The openness of psychotherapists towards patient characteristics suggests that BC in outpatient care may target a broad patient population.